Избранное: в 2-х книгах (Сергей Орлов ; [редактор И. Исакович ; оформление художника А. Третьякова]) - Орлов Сергей Сергеевич (1971)
Экземпляры: Аб (1971) / Инвентарный номер: 48809с / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: О-66 / ББК: 84(2Рос=Рус)6